Recurrent renal secondary hyperparathyroidism caused by supernumerary mediastinal parathyroid gland and parathyromatosis: A case report - Li, Longfei; He, Chenchen; Cheng, Guangming; Cao, Junying; Wang, Chunhui; Tang, Yufu; Zhang, Wei (Frontiers in Surgery, 2023)
Background: Surgical parathyroidectomy (PTX) is necessary for those patients with severe and progressive secondary hyperparathyroidism (SHPT) refractory to medical treatment. Recurrence of SHPT after PTX is a serious clinical problem after PTX. Both of supernumerary mediastinal parathyroid gland and parathyromatosis are the rare causes of recurrent renal SHPT. We reported a rare case of recurrent renal SHPT due to supernumerary mediastinal parathyroid gland and parathyromatosis. Case presentation: A 53-year-old man underwent total parathyroidectomy with autotransplantation (TPTX+AT) due to the drug-refractory SHPT 17 years ago. In the last 11 months, the patient experienced symptoms including bone pain and skin itch and the serum intact parathyroid hormone (iPTH) level elevated to 1587 pg/ml. Ultrasound （US）detected two hypoecho lesions located at the dorsal area of right lobe of thyroid gland, and both of lesions presented as characteristics of hyperparathyroidism in contrast-enhanced ultrasound (CEUS). And 99mTc-MIBI/SPECT detected a nodule in the mediastinum. A reoperation involved a cervicotomy for excising parathyromatosis lesions and the surrounding tissue and a thoracoscopic surgery for resecting a mediastinal parathyroid gland. According to a histological examination, two lesions behind the right thyroid lobe and one lesion in the central region had been defined as parathyromatosis. A nodule in the mediastinum was consistent with hyperplastic parathyroid. The patient has remained well for 10 months with the alleviated symptoms and the stabilized iPTH levels in the range 123-201 pg/ml. Conclusion: Although rare, recurrent SHPT may be caused by a coexistence of both SPGs and parathyromatosis, which should be received more attention. The combination of imaging modalities is important for re-operative location of parathyroid lesions. To successfully treat parathyromatosis, all the lesions and the surrounding tissue must be excised. Thoracoscopic surgery for the mediastinal parathyroid glands is feasible with minimal invasive.